Nutrition Counseling to Improve Mothers’ Knowledge and Behavior in Supporting Toddlers’ Growth and Development at Perawatan Health Center, Blangkejeren City (JURNAL PENGMAS KESTRA (JPK), 2025)
Imbalanced nutrition among toddlers remains a significant public health challenge in Indonesia, despite a declining national trend in stunting prevalence. Issues such as malnutrition, undernutrition, and micronutrient deficiencies continue to threaten optimal growth in children under five, potentially affecting physical and cognitive development as well as future human resource quality. Stunting and wasting are key indicators for assessing child nutritional status, while improving maternal capacity in childcare, particularly from pregnancy to the child’s first two years, has become a strategic priority in public health policies. Nutritional counseling serves as an essential educational intervention to enhance mothers’ knowledge and skills in applying balanced nutrition principles, thereby promoting behavioral changes in daily feeding practices. This Community Service Program aimed to improve maternal knowledge and behavior regarding balanced nutrition and to empower the community through participatory educational methods. The activity was conducted at the Perawatan Health Center in Blangkejeren with 20 mothers of toddlers selected using purposive sampling. The intervention followed a pre- and post-counseling design, incorporating interactive presentations, group discussions, and practical simulations of proper feeding practices. Evaluation instruments included pre- and post-test questionnaires, educational media (posters, leaflets, visual aids), and observation sheets to monitor participant engagement. Results indicated a significant improvement in knowledge, with high-level knowledge increasing from 10 % to 65 % and low-level knowledge decreasing from 40 % to 5 %. Positive feeding behaviors rose from 15 % to 75 %, fair behaviors decreased from 55 % to 25 %, and poor behaviors were eliminated. Participant engagement was high, with 75 % actively asking questions, 100 % joining discussions, 90 % performing feeding simulations, and 85 % providing feedback. These findings demonstrate that interactive and participatory nutritional counseling effectively enhances maternal understanding and practices, thereby supporting optimal toddler growth and development.